Unlocking Economic Potential: Sectors to Focus on in West Nusa Tenggara - Unik Lestari; Suharno Suharno (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The research objective is to find out what economic sectors can be further developed to support economic growth in West Nusa Tenggara Province. This study uses shift-share analysis. This study collected data from GRDP data at constant prices derived from the publication of the Central Bureau of Statistics of West Nusa Tenggara Province and National Indonesia in 2017-2023. The results of the shift-share analysis show that the economic sectors that have rapid and progressive growth and have the potential to improve the regional competitiveness of West Nusa Tenggara Province are the electricity and gas procurement sector and the financial and insurance services sector.